THE IMPLEMENTATION OF GOOD CORPORATE GOVERNANCE PRINCIPLES ON CORPORATE SOCIAL RESPONSIBILITY PROGRAMS OF TOURISM INDUSTRY AT MALANG RAYA (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study aims to provide an overview of the governance of Corporate Social Responsibility in the entertainment and tourism industry in the city of Malang, based on the principles of Good Corporate Governance which consists of transparency, accountability, responsibility, independence and justice that have a role in improving the welfare of society in the industry entertainment and tourism in the city of Malang This research approach is qualitative descriptive. Research locations in the city of Malang with the assumption that the city has a sufficient number of entertainment venues and tourist rides compared to other cities in East Java Province. The results of the research show that the management of Corporate Social Responsibility is still far from the expectations of the local community. The management of the entertainment and tourism industry with the principles of good corporate governance needs to be enhanced through the control and regulation of business entities to create added value and to keep the entertainment and tourism industry in maintained its existence. This needs to be done so that the perceptions of stakeholders of investors, communities and governments in maintaining and improving the sustainability of the entertainment and tourism industry operations in the future.